Perancangan dan Implementasi Drone Flysurveil Berbasis IoT untuk Sistem Pengawasan Otomatis - Triantono, Gatot; Al-Khowarizmi, Al-Khowarizmi (Lembaga Riset Mutiara Akbar, 2025)
The development of drone technology has had a significant impact on various sectors, including agriculture, security, and environmental monitoring. The Flysurveil drone was developed under the P2MW program as an innovative solution in IoT-based surveillance systems. This study aims to analyze the Flysurveil drone production process and identify technical challenges encountered in its development. The research methods used include literature review, observation, and technical analysis of the components and systems used in drone production. The results show that the Flysurveil drone production process includes several main stages, namely design, component selection, assembly, and testing. The main components used include Arduino and ESP32 microcontrollers, GPS modules, cameras, and brushless motors controlled by ESCs. However, several technical challenges were encountered, such as optimizing battery life, control system stability, and limitations in real-time data communication. This research is expected to provide insights for drone developers in improving production efficiency and the quality of drone-based surveillance systems. In addition, this research also contributes to the development of more adaptive and competitive drone technology in both domestic and global markets.